Magnetic-responsive polysaccharide hydrogels as smart biomaterials: Synthesis, properties, and biomedical applications - Fragal E.H. (2022)
© 2022 Elsevier LtdThis review reports recent advances in polysaccharide-based magnetic hydrogels as smart platforms for different biomedical applications. These hydrogels have proved to be excellent, viable, eco-friendly alternative materials for the biomedical field due to their biocompatibility, biodegradability, and possibility of controlling delivery processes via modulation of the remote magnetic field. We first present their main synthesis methods and compare their advantages and disadvantages. Next, the synergic properties of hydrogels prepared with polysaccharides and magnetic nanoparticles (MNPs) are discussed. Finally, we describe the main contributions of polysaccharide-based magnetic hydrogels in the targeted drug delivery, tissue regeneration, and hyperthermia therapy fields. Overall, this review aims to motivate the synthesis of novel composite biomaterials, based on the combination of magnetic nanoparticles and natural polysaccharides, to overcome challenges that still exist in the treatment of several diseases.